The role of prophylactic antibiotics in nasal packing for epistaxis - ali, Mohamed ibrahim; raheem, Chassan hassan (AL-Kindy College Medical Journal, 2019)
Background: This study is to evaluate the necessity of prescribing prophylactic antibiotics for nasal packing in spontaneous epistaxis. There are few published papers of infective complications in such patients. Methods: This prospective study analysed 149 consecutive patients admitted to AL-Kindy teaching hospital with spontaneous, epistaxis, who underwent nasal packing over 2 years period . in the first year, 78 patients received prophylactic antibiotics , In the second year 71 patients were not given prophylatic antibiotics. Exclusion criteria included antibiotics prescribed for unrelated pathology and post-operative epistaxis. Signs and symptoms of acute otitis media, sinusitis and toxic shock syndrome were assessed using clinical examination and a questionnaire. Results: :Fourteen out of 149 patients experienced otalgia, mostly following posterior nasal packing. No patient in both groups had evidence of any infective complication. Conclusion: we do not recommend the use of prophylactic antibiotics for patients undergoing nasal packing for spontaineous epistaxis.